Beyond Transit: Tunisia as Imagined, Experienced, and Negotiated by Migrant Women from West and Central Africa - Asma Ben Hadj Hassen (Mashriq & Mahjar)
This article critically examines spatial categories such as countries of origin, transit, and destination within migration discourse, arguing that these classifications fail to capture the complexity of migrants’ trajectories and aspirations. By centering the lived experiences of two sub-Saharan migrant women, Fatou and Christine, the study draws on ethnographic fieldwork in Tunisia and a feminist methodological approach to explore how migrant women navigate non-linear and ambivalent paths shaped by legal precarity, gendered labor, motherhood, and evolving migration policies. For some women migrants, this North African country, which has been undergoing radical political change since 2011, can be seen as a destination for work or study but can also become a place of transit for varying lengths of time and vice versa. Rather than progressing toward Europe or returning home, their journeys reflect constant negotiation, compromise, and strategic adaptation. Mobilizing Camille Schmoll’s concept of autonomy in tension as a form of constrained agency enacted under structural vulnerability, the article highlights how migrant women engage in everyday practices of resistance and care within extended periods of uncertainty. I argue that, beyond their simple status as transit or settled migrants, these women are transforming and being transformed by the Tunisian space. It is a space where they embark on a process of learning and self-assertion. By foregrounding their voices, this work contributes to feminist migration studies and offers a grounded critique of the transit paradigm.